Palladium-Catalyzed Synthesis of β,β-Diaryl α,β-Unsaturated Ketones - Zheng, Yi-lin; Xiao, Li; Xie, Qiong; Shao, Li-ming (Synthesis, 2019)
We herein describe a versatile palladium-catalyzed synthesis of β,β-diaryl α,β-unsaturated ketones. A broad range of aryl halides react with β-arylbutanones to afford biologically useful, symmetrical and unsymmetrical ketones. The use of 4,5-diazafluoren-9-one and oxygen makes this one-pot reaction more applicable. A plausible mechanism involving palladium-catalyzed oxidative Heck-type cross-coupling is also proposed.
Keywords: ketones; palladium; 4,5-diazafluoren-9-one; oxidation; cross-coupling